2020
DOI: 10.1186/s13021-020-00148-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling sediment diagenesis processes on riverbed to better quantify aquatic carbon fluxes and stocks in a small watershed of the Mid-Atlantic region

Abstract: Background Despite the widely recognized importance of aquatic processes for bridging gaps in the global carbon cycle, there is still a lack of understanding of the role of riverbed processes for carbon flows and stocks in aquatic environments. Here, we added a sediment diagenesis and sediment carbon (C) resuspension module into the SWAT-C model and tested it for simulating both particulate organic C (POC) and dissolved organic C (DOC) fluxes using 4 years of monthly observations (2014–2017) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 79 publications
0
5
0
2
Order By: Relevance
“…Watershed models that explicitly integrate terrestrial and aquatic carbon cycling processes are being developed to quantify the burial of particulate organic carbon (OC) in rivers. For example, Qi et al [476,477] incorporated OC deposition, resuspension, and diagenesis processes in the soil and water assessment tool and showed that a significant fraction of terrestrially originated POC is deposited on the bed of small streams and further decomposes into CO 2 and CH 4 . These results indicate that the inclusion of C burial in rivers and streams would improve the accounting of global C burial in inland waters.…”
Section: Carbon Burialmentioning
confidence: 99%
“…Watershed models that explicitly integrate terrestrial and aquatic carbon cycling processes are being developed to quantify the burial of particulate organic carbon (OC) in rivers. For example, Qi et al [476,477] incorporated OC deposition, resuspension, and diagenesis processes in the soil and water assessment tool and showed that a significant fraction of terrestrially originated POC is deposited on the bed of small streams and further decomposes into CO 2 and CH 4 . These results indicate that the inclusion of C burial in rivers and streams would improve the accounting of global C burial in inland waters.…”
Section: Carbon Burialmentioning
confidence: 99%
“…For example, the Soil and Water Assessment Tool (SWAT) is being used within the USDA Conservation Effects Assessment Project (CEAP) and EPA Hydrologic And Water Quality Modeling System (HAWQS) to support national scale conservation and water quality studies and policymaking. The SWAT model has been continuously modified to adapt to new socioeconomic and environmental conditions by adding improved physical/chemical functions and considering more diverse management practices. Numerous examples of SWAT modifications and applications can be found at: . For example, the standard SWAT used a simple regression method to estimate soil temperature and FTCs as a function of air temperature, soil depth, and soil cover (both residue and snow), in which phase changes of soil water and snow insulation effects are not well addressed. ,, Such a simple FTC representation exhibited large biases in reproducing soil temperatures observed at sites of the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…A hydrologic model coupled with a module that represents the fate and transport of carbon was found to effectively capture dissolved and particulate organic carbon loads [25]. A recent study further improved the carbon cycling within in-streams to better predict carbon fluxes [26]. A model coupled with a water temperature module showed improved predictions of water quality variables affected by water temperature [27].…”
Section: Introductionmentioning
confidence: 99%